1993
DOI: 10.1063/1.858663
|View full text |Cite
|
Sign up to set email alerts
|

Optimal perturbations and streak spacing in wall-bounded turbulent shear flow

Abstract: The mean streak spacing of approximately 100 wall units that is observed in wall-bounded turbulent shear flow is shown to be consistent with near-wall streamwise vortices optimally configured to gain the most energy over an appropriate turbulent eddy turnover time. The streak spacing arising from the optimal perturbation increases with distance from the wall and is nearly independent of Reynolds number, in agreement with experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
230
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(249 citation statements)
references
References 9 publications
17
230
1
1
Order By: Relevance
“…Of particular importance has been the recognition that linear mechanisms play a key role in controlling the transition to turbulence at low Reynolds number (Trefethen et al 1993;Henningson & Reddy 1994), as well as generating and sustaining the dynamically important coherent structures that characterize wall turbulence (e.g. Butler & Farrell 1993;Schoppa & Hussain 2002;Kim 2011). As a result, the application of concepts from control theory has led to the design of many successful control strategies that delay the onset of turbulence (Joshi, Speyer & Kim 1997), relaminarize turbulent flows (Högberg, Bewley & Henningson 2003;Sharma et al 2011), or reduce turbulent kinetic energy (Lim & Kim 2004).…”
Section: Feedback Flow Controlmentioning
confidence: 99%
“…Of particular importance has been the recognition that linear mechanisms play a key role in controlling the transition to turbulence at low Reynolds number (Trefethen et al 1993;Henningson & Reddy 1994), as well as generating and sustaining the dynamically important coherent structures that characterize wall turbulence (e.g. Butler & Farrell 1993;Schoppa & Hussain 2002;Kim 2011). As a result, the application of concepts from control theory has led to the design of many successful control strategies that delay the onset of turbulence (Joshi, Speyer & Kim 1997), relaminarize turbulent flows (Högberg, Bewley & Henningson 2003;Sharma et al 2011), or reduce turbulent kinetic energy (Lim & Kim 2004).…”
Section: Feedback Flow Controlmentioning
confidence: 99%
“…The importance of this nondimensional interval was recognized by Lee et al (1990) who provide estimates which are shown in Figure 4. Butler and Farrell (1993) showed that the perturbations in the turbulent sublayer that optimize energy in an eddy turnover time characteristic of sublayer turbulence have the observed z + = 100 streak spacing.…”
Section: D the Role Of Finite Coherence Time In Shear Turbulencementioning
confidence: 99%
“…This result implies that streaks arise naturally from small random disturbances and explains the ubiquity of streaks in shear flow. The mechanism responsible for selecting the z + ≈ 100 spanwise spacing of the sublayer streaks was subsequently clarified by Butler and Farrell (1993). Their results were obtained making use of optimal perturbation theory which provides a constructive method for finding the perturbation with the greatest increase in energy over a specified interval of time (B&F).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations